Hereditary Homozygous Heparin Cofactor II Deficiency and the Risk of Developing Venous Thrombosis - Villa, Piedad; Aznar, Justo; Vaya, Amparo; España, Francisco; Ferrando, Fernando; Mira, Yolanda; Estellés, Amparo (Thrombosis and Haemostasis, 1999)
Heparin cofactor II (HCII) is a specific inhibitor of thrombin in the presence of heparin or dermatan sulphate. Although there have been reports on families in which a heterozygous HCII deficiency is associated with thromboembolic events, several epidemiological studies revealed that heterozygous HCII deficiency is as prevalent among healthy subjects as it is among patients with deep venous thrombosis (DVT). It is therefore not yet clear whether HCII is or is not a thrombotic risk factor.We analyze and describe in an extended family the biochemical and genetic thrombophilic risk factors and evaluate the potential thrombotic risk involved in homozygous and heterozygous HCII deficiency, either alone or associated with other thrombotic or circumstantial risk factors. The propositus has had three episodes of DVT and a pulmonary embolism. During the first episode of DVT the patient was diagnosed as having AT deficiency. Later, a functional and antigenic HCII deficiency, compatible with the homozygous form, was detected. The family study shows that both the propositus and her sister have homozygous HCII deficiency and that 12 of the 27 family members have heterozygous HCII deficiency.This is possibly the first case report on a homozygous phenotype for the HCII deficiency with, in addition, partial AT deficiency. The propositus has suffered several thrombotic events, unlike the other 12 family members with heterozygous HCII deficiency and her sister, who is also homozygous for this disorder. We suggest that HCII deficiency may play a limited in vivo role as a thrombotic risk factor unless associated with AT deficiency or another congenital thrombotic risk factor.